Políticas de incentivos e a exposição ao risco estratégico: o ponto de vista de conselheiros de administração - Varreira, Marcelo da Silva (Universidade do Vale do Rio dos Sinos, 2013)
The application of monetary and non monetary incentives to executives in order to obtain a performance business, short or long term, are corporate governance mechanisms for aligning the interests of shareholders, and majority owner (principal) and managers (agents). As this alignment adjusting the role of Board of Directors and committees of support as risk and return are key. Depending on the setting of the system, there may be a strategic risk exposure to greater or lesser degree. In Brazil, as perceptions of board members, this mechanism is not regulated for the purpose of regular exposure to strategic risk and incentive policies are aligned generally in the short term, as the desired performance, leading to control costs and monitoring. Moreover, some peculiarities Brazilian models leads to the need for adequate incentive to Brazil, being the components of incentive usual in Europe and the United States, in some cases, conflicting with the Brazilian labor legislation and tax.
Keywords: Política de incentivos; Performance; Exposição ao risco estratégico; Conselho de administração; Longo e curto prazo; Executive compensation policy; Strategic risk exposition; Administration board; Long and short term; ACCNPQ::Ciências Sociais Aplicadas::Administração